Pulmonary Embolism in COVID-19: Trends from a Single-Center Study Across Ten Pandemic Waves in Romania - Alexandra Herlo; Adelina Raluca Marinescu; Talida Georgiana Cut; Ruxandra Laza; Adina Maria Marza; Claudia Raluca Balasa Virzob; Cristian Iulian Oancea; Lucian-Flavius Herlo; Ioana-Melinda Luput-Andrica; Voichita Elena Lazureanu (Microorganisms)
The COVID-19 pandemic has significantly impacted global health, with pulmonary embolism (PE) emerging as a critical complication due to the hypercoagulable state induced by SARS-CoV-2 infection. Despite advancements in prevention and treatment, PE remains a major cause of morbidity and mortality in COVID-19 patients. This study analyzes the trends, outcomes, and contributing factors of PE across ten pandemic waves in Romania, highlighting the evolving clinical burden and management approaches. This retrospective observational study was conducted on confirmed COVID-19 patients that also developed PE, who were admitted to “Victor Babeș” Hospital and Municipal Emergency Hospital in Timișoara, Romania. Data on demographics, clinical features, inflammatory markers, comorbidities, and treatment were collected from medical records. Statistical analyses, including ANOVA and Kaplan–Meier survival analysis, were conducted to evaluate trends and survival outcomes over time. The study included 166 patients, with a mean age of 67.26 ± 13.57 years. Mortality peaked at 50% in Wave 1, declined to 12% in Wave 7, and increased again to 28% in Wave 10. Intubation rates varied, with a high of 29% in Wave 6 and a low of 12% in Wave 8. Lung involvement was the most severe in Wave 4 (mean 0.54 ± 0.18) but improved in later waves, reaching a mean of 0.24 ± 0.12 in Wave 8. This study highlights the dynamic trends in PE during the COVID-19 pandemic in Romania. Improved clinical management, vaccination, and adaptive healthcare strategies contributed to better outcomes in later waves.